Diagnóstico estratégico das desigualdades socioespaciais na acessibilidade ao trabalho em Fortaleza - Sousa, Francelino Franco Leite de Matos (2019)
The socio-spatial inequalities in access to opportunities, understood as resulting from differences in the levels of accessibility among groups of people residing in distinct regions of the city, with different socioeconomic characteristics, or between present and future generations, should be considered strategic urban problems. These problems must be diagnosed and treated within an integrated urban planning process whose social justice foundation is the principle of egalitarianism. Such inequalities in access to urban activities can result from restrictions imposed on the accessibility levels of different groups, originated in the activities, land-use, and transport subsystems. In Fortaleza, this dissertation’s case study, it is considered that populational socioeconomic differences are one of the main causes of inequalities in access to jobs. Its low-income segments, dependent on public transit, have been forced to live in peripheral areas, far from employment opportunities; which, in turn, are concentrated in the city’s central region, largely inhabited by high-income groups and with a high-density road supply. Therefore, this research started with the contextualization of this problematic setting by the description of Fortaleza’s urban development in the first two decades of the 21st century, allowing to raise causality hypotheses that the spatial mismatch between housing and jobs, as well as the inefficient spatial distribution of transport infrastructure supply, have contributed to perpetuate socio-spatial inequalities in accessibility to work in the city. These hypotheses were analyzed through the construction and implementation of a method for characterization and diagnosis of the inequality problems. The proposed method was based on the measurement of the past, present and future levels of accessibility to job opportunities for low- and high-income groups, applying an utility based indicator obtained from calibration and validation of the integrated model TRANUS for Fortaleza. The spatial dependency relationships were then investigated with the use of geographically weighted regression models. It is argued in this work that the effort to understand the socio-spatial inequalities in urban accessibility should be taken before the definition and prioritization of strategic and tactical objectives, as well as the proposition and evaluation of interventions in the land-use and transport subsystems, therefore producing a knowledge that will endorse a more effective negotiation of urban stakeholders’ conflicting interests, moving towards the greater goals of improving quality of life and social justice.